Bis(benzylsulfanyl)methane - Yang, Hojin (International Union of Crystallography, 2010)
In the title compound, C(15)H(16)S(2), the structure of the dithioalkyl chain is a helix with an all-cis conformation. The dihedral angle between the mean planes of the terminal aromatic rings is 74.60 (4)°. In the crystal structure, weak C—H⋯π interactions contribute to the stabilization of the packing.